2018
DOI: 10.1097/qai.0000000000001773
|View full text |Cite
|
Sign up to set email alerts
|

Sex Education and HIV Testing Among Young Men Who Have Sex With Men: Findings From the 2006–2010 and 2011–2015 National Survey of Family Growth

Abstract: Tailored sex education by parent(s) and health care providers related to HIV/AIDS seems to significantly increase the likelihood of HIV testing among YMSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…3 Although there has been little epidemiological research on HIV incidence among adolescent men who have sex with men (AMSM), 2 studies suggest incidence is high, particularly among African American and Hispanics and/or Latinos (3%-5% per year). 4,5 Few studies have described the rate of testing among MSM ,18 years old, and with few exceptions, 6-9 many of the available studies combine data from teenagers aged 18 and younger with adults as old as 24, 10,11 which is a standard approach in national HIV surveillance reports. 3 Even fewer studies have explored differences in testing behaviors, and their correlates, among racially and/or ethnically diverse AMSM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Although there has been little epidemiological research on HIV incidence among adolescent men who have sex with men (AMSM), 2 studies suggest incidence is high, particularly among African American and Hispanics and/or Latinos (3%-5% per year). 4,5 Few studies have described the rate of testing among MSM ,18 years old, and with few exceptions, 6-9 many of the available studies combine data from teenagers aged 18 and younger with adults as old as 24, 10,11 which is a standard approach in national HIV surveillance reports. 3 Even fewer studies have explored differences in testing behaviors, and their correlates, among racially and/or ethnically diverse AMSM.…”
mentioning
confidence: 99%
“…27 One recent study found that physician discussions about HIV and testing and parent-child discussions about how to prevent HIV were each significantly associated with ever being HIV tested among MSM ages 15 to 24. 10 Finally, the information-motivationbehavioral skills (IMB) model 28 for HIV prevention suggests key factors that are influential over testing. In adult MSM, [29][30][31] this model has shown that individuals who have correct knowledge about HIV, are stimulated by emotional and/or situational responses (eg, fear and vulnerability), and have the skills to navigate the process are more likely to complete HIV testing.…”
mentioning
confidence: 99%
“… 49 In the United States, parent-based sex education could increase adolescent engagement in HIV testing and condom use. 50 However, even in developed countries, such as the United States, sex education led by parents is not common, as one-third of young MSM had never discussed sex topics with their parents. 50 Tailored sex education by parents could increase the likelihood of HIV testing among student MSM.…”
Section: Discussionmentioning
confidence: 99%
“… 50 However, even in developed countries, such as the United States, sex education led by parents is not common, as one-third of young MSM had never discussed sex topics with their parents. 50 Tailored sex education by parents could increase the likelihood of HIV testing among student MSM. 50 Therefore, sex education led by parents is an issue that requires attention from both developed and developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…HIV incidence among 16-to 17-year-old Chicago ASMM has been estimated at 5.2/100 person-years [2], and a three-city study reported incidence of 3.4/100 person-years among ASMM [3]. ASMM are also less likely to be tested for HIV compared to adult men who have sex with men (MSM) [4,5].…”
mentioning
confidence: 99%